Quality of Life Evaluation as Decision Support in Public Administration for Innovation and Regions Development - Šanda, Martin; Křupka, Jiří (My University, 2018)
This contribution deals with Quality of Life (QL) issues and QL evaluation. The objective of this contribution is to develop a model for QL evaluation for the Czech Republic (CR) regions. This model shall be used for decision-making by regional administrations in the area of grants allocation. These grants shall be grants for innovation and for regional development in selected areas. The objective of the model is to reach fairness and to decrease disparities between individual regions of the CR. Selected methods of Rule-based systems (RBS) shall be used in this model. An important aspect of this model is to define indicators to be used for the QL evaluation and the indicators’ weights. These weights have been defined directly by the CR inhabitants by means of a questionnaire-based survey. Wisdom of the Crowd (WoC) approach has been used to acquire the above-mentioned indicators. The objective of the model is to evaluate, based on predefined indicators, the QL in individual regions and based on the results of this evaluation to recommend grants allocation policy for individual regions for development in the given area and thus to reduce disparity between individual regions and by doing that to increase the overall competitiveness of the CR.
Quality of Life Evaluation as Decision Support in Public Administration for Innovation and Regions Development
Keywords: decision support; grant allocation; quality of life; wisdom of the crowd; decision support; grant allocation; quality of life; wisdom of the crowd